Meso-mechanical properties and energy evolution characteristics of fractured sandstone under mining stress path - Xuefeng LI; Chao PAN; Juncai CAO; Lin YAN; Tengfei HAN; Xu HONG (Meikuang Anquan, 2025)
In order to explore the differences in deformation failure characteristics and energy evolution of fractured rock masses under the mining stress path, triaxial loading and unloading tests were conducted on sandstone samples with different fracture lengths and angles using PFC numerical simulation. The causes of sample failure are analyzed through the failure modes of the samples, and the transformation relationship between energy storage and dissipation is characterized by the energy release coefficient k. The results show that: with the increase of fracture length, the peak strength and elastic modulus of sandstone decrease, while with the increase of fracture angle, the peak strength and elastic modulus of sandstone first decrease and then increase; four types of cracks, namely coplanar shear cracks, anti-shear cracks, tensile cracks and far-field tensile cracks, are produced during specimen failure, and the main cause of specimen failure is the expansion of shear cracks from the tip to the end of the prefabricated cracks; the shear cracks show an evolution trend of coplanar-non-coplanar-coplanar with the fracture length, while the shear cracks show an evolution trend of coplanar-non-coplanar with the fracture angle; the influence of prefabricated fractures on the surrounding displacement field increases with the increase of fracture length and shows a change of first increasing and then decreasing with the increase of fracture angle; the energy release coefficient k shows a changing trend of decreasing-increasing-decreasing-steady decreasing, and the failure strength of the rock can be evaluated by the energy coefficient kc at the peak stress based on energy evolution.